The effects of tax reforms to address the debt-equity bias on the cost of capital and on effective tax rates - Christoph Spengel; Jost Henrich Heckemeyer; Rainer Bräutigam; Katharina Nicolay; Oliver Klar; Kathrin Stutzenberger (Office for Official Publications of the European Communities, 2016)
[Main objectives] Corporate income tax systems usually discriminate between the different sources of finance: They favour debt over equity financing since interest costs are deductible for tax purposes whereas there is no equivalent relief for equity-financed investments. This unequal treatment might cause economic problems such as excessive leverage in the corporate sector and an associated increased vulnerability to economic crises, disadvantages for firms with restricted access to external funds and profit shifting incentives. To achieve an equal treatment of debt and equity financing, either an additional deduction for equity financing could be granted or the current deduction for interest expenses could be disallowed. A disallowance of interest expenses could be achieved by the interest deduction limitation rules which are already employed in several Member States. Other far-reaching, fundamental tax reforms to address the current debt bias are represented by the Comprehensive Business Income Tax (CBIT), Allowance for Corporate Equity (ACE), Allowance for Corporate Capital (ACC) and Cost of Capital Allowance (COCA). The present study provides an in-depth analysis of the effects of these different reform options on effective tax burdens in the EU28 Member States. Moreover, the study gives guidance to which extent current income tax rates at corporate and personal level would have to be adjusted for a revenue neutral implementation of fundamental tax reforms. On the basis of stylised model computations, this study informs about whether different fundamental tax reforms could, in principle, manage to address the debt bias and promote investment, possibly in a revenue neutral way. The main objectives of the study can be summarised as follows: * Analyse current interest deduction limitation rules in the EU28 Member States and assess the effect of interest deduction limitation rules on effective tax rates; * Provide insights on the effects of the fundamental tax reform options on current tax systems; * Consider a revenue-neutral implementation of the reforms and possible consequences for the level of investment in the EU28 Member States.
Keywords: 330